2020
DOI: 10.1101/2020.10.06.327957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Failures of nerve regeneration caused by aging or chronic denervation are rescued by restoring Schwann cell c-Jun

Abstract: After nerve injury, myelin and Remak Schwann cells reprogram to repair cells specialized for regeneration. Normally providing strong regenerative support, these cells fail in aging animals, and during the chronic denervation that results from the slow growth of axons. This impairs axonal regeneration and causes a significant clinical problem. In mice, we find that repair cells express reduced c-Jun protein as the regenerative support provided by these cells declines in aging animals and during chronic denervat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…The copyright holder for this preprint this version posted September 8, 2022. ; https://doi.org/10.1101/2022.08.25.505298 doi: bioRxiv preprint (GDNF). Previous studies have demonstrated the decreased ability of aged mice to regenerate nerves post-injury when compared to their younger counterparts as a result of decreased c-Jun expression [17], and neuropathic diseases such as CIDP are characterized by a loss of SC plasticity [57]. Notably, qPCR of c-Jun in scWAT revealed almost no difference between young and old mice while displaying upregulation in obese BTBR ob/ob mice (Figure 6).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The copyright holder for this preprint this version posted September 8, 2022. ; https://doi.org/10.1101/2022.08.25.505298 doi: bioRxiv preprint (GDNF). Previous studies have demonstrated the decreased ability of aged mice to regenerate nerves post-injury when compared to their younger counterparts as a result of decreased c-Jun expression [17], and neuropathic diseases such as CIDP are characterized by a loss of SC plasticity [57]. Notably, qPCR of c-Jun in scWAT revealed almost no difference between young and old mice while displaying upregulation in obese BTBR ob/ob mice (Figure 6).…”
Section: Discussionmentioning
confidence: 85%
“…A hallmark feature of SCs is their ability to shift towards a repair phenotype in response to injury, releasing neurotrophic factors such as BDNF and glial cell line-derived neurotrophic factor Schwann Cells in Subcutaneous Adipose Tissue (GDNF). Previous studies have demonstrated the decreased ability of aged mice to regenerate nerves post-injury when compared to their younger counterparts as a result of decreased c-Jun expression [17], and neuropathic diseases such as CIDP are characterized by a loss of SC plasticity [57]. Notably, qPCR of c-Jun in scWAT revealed almost no difference between young and old mice while displaying upregulation in obese BTBR ob/ob mice (Figure 6).…”
Section: Schwann Cells In Subcutaneous Adipose Tissuementioning
confidence: 85%
See 2 more Smart Citations
“…Since RSC96 is a transformed cell line, further studies using primary Schwann cells need to be carried out to confirm these results. Nevertheless, SHH has been shown to stimulate in Schwann cells activation of c–Jun, a downstream transcription factor of the MAP kinases ( Wagstaff et al, 2020 ). Therefore, the pathways via SHH, c–Jun, and MAPK seem to be interconnected.…”
Section: Melatonin Regulates Schwann Cell Proliferation and Migration...mentioning
confidence: 99%